2013
DOI: 10.1002/jhet.1807
|View full text |Cite
|
Sign up to set email alerts
|

Improved Negishi Cross‐Coupling Reactions of an Organozinc Reagent Derived from l‐Aspartic Acid with Monohalopyridines

Abstract: The Negishi cross-coupling reaction of an organozinc derivative prepared from protected L-aspartic acid with monohalopyridines was improved by employing a combination catalyst of Pd 2 (dba) 3 and P(2-furyl) 3 and removing an extra Zn from the organozinc reagent via centrifugation. The reactivity of halogenated pyridines (Cl, Br, I) with substituents at the C2, C3, and C4 positions of the pyridine ring was investigated, and it was found that the use of 4-iodopyridine as a substrate gave the best yield (90%) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…After insertion of zinc into the protected γ-iodoalkylated l-glycine 8, the excess zinc was removed from the organozinc reagent by centrifugation. [19] The cross-coupling reaction was then conducted by using 4 mol-% tris(dibenzylideneacetone)dipalladium(0) Scheme 3. First attempts at stepwise cross-coupling reactions using 6.…”
Section: Resultsmentioning
confidence: 99%
“…After insertion of zinc into the protected γ-iodoalkylated l-glycine 8, the excess zinc was removed from the organozinc reagent by centrifugation. [19] The cross-coupling reaction was then conducted by using 4 mol-% tris(dibenzylideneacetone)dipalladium(0) Scheme 3. First attempts at stepwise cross-coupling reactions using 6.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014 Usuki et al reported the improved Negishi crosscoupling of halopyridines with an iodozinc species derived from aspartic acid (Scheme 15). 56 Previous work such as that reported by Tuttle et al (Scheme 13) had shown that yields for pyridine cross-coupling products significantly lagged behind their non-heteroaromatic equivalents. 57 After extensive reaction optimisation, a catalytic system of Pd 2 (dba) 3 in combination with a P(2-furyl) 3 ligand was shown to be the best for the cross-coupling of halopyridines, with a 90% yield recorded in the reaction between 4-iodopyridine and 36.…”
Section: Synthesis Of Heteroaromatic Amino Acidsmentioning
confidence: 95%
“…The introduction of iodoalkylated L-glycine 9 at the 3,5-positions of the obtained 12 was then attempted via a Negishi cross-coupling reaction using the catalyst Pd-PEPP-SI-IPr, which was developed by Organ and co-workers. 23 The reaction was performed using an improved procedure 24 that involved removal of the excess Zn from the organozinc reagent via centrifugation, followed by the coupling using 20 mol% Pd-PEPPSI-IPr catalyst at 60 °C to afford the tricoupled pyridine 5 in 83% yield without any dicoupled compound. Interestingly, the yields of the coupling reactions in the present study were greater than those obtained during the synthesis of desmosine 1 (Sonogashira: 58%, Negishi: 60%).…”
Section: Chemical Synthesis Of Desmosine-chmentioning
confidence: 99%